Rectal Metastases from Squamous Cell Carcinoma: A Case Report and Review of the Literature - S. Cedrés; N. Mulet-Margalef; M. A. Montero; P. Martinez; A. Martínez; E. Felip (Case Reports in Medicine)
Non-small-cell lung cancer (NSCLC) represents 85% of lung cancer. The most frequent sites of distant metastasis are the liver, adrenal glands, bones and brain. Gastrointestinal metastases are uncommon and rectal metastases are extremely rare. Here we report a case of squamous cell carcinoma of the lung with rectal metastases.